Data-Driven Recursive Least Squares Estimation for Model Predictive Current Control of Permanent Magnet Synchronous Motors - Brosch, Anian; Hanke, Sören; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)

Emulation of Microgrids for Research and Validation of Control and Operation Strategies - Stille, Karl Stephan Christian; Weber, Daniel; Lange, Jarren; Vogt, Thorsten; Wallscheid, Oliver; Böcker, Joachim (2020 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

A 3,6 kW Single-Stage LLC Converter Operating in Half-Bridge, Full-Bridge and Phase-Shift Mode for Automotive Onboard DC-DC Conversion - Rehlaender, Philipp; Grote, Tobias; Tikhonov, Sergey; Mario, Schröder; Schafmeister, Frank; Böcker, Joachim (PCIM Europe digital days 2020)
Automotive DC-DC converters linking the traction battery to the auxiliary battery are characterized by the wide input and output voltage ranges resulting from the varying state-of-charge of the traction and auxiliary battery. The wide voltage transfer ratio needs to be covered for the entire load range conventionally requiring two-stage converter architectures. Considering a less complex single-stage solution potentially enabling cost and weight advantages, traditional LLC converters are unsuitable topologies since it results in a too wide operating frequency range. Most alternative topology candidates show comparable difficulties. To overcome this issue, the gain range of the LLC with full-bridge inverter can be extended by operation in half-bridge mode for low voltage transfer ratios. Phase-shift operation is utilized for intermediate gains and low loads. This paper describes a detailed design methodology for the resonant tank. The experimental results with a peak efficiency of 96.5 % and a power density of 2.1 kW/l prove the proposed concept.

Two-Stage Automotive DC-DC Converter Design with Wide Voltage-Transfer Range Utilizing Asymmetric LLC Operation - Rüschenbaum, Tobias; Rehlaender, Philipp; Ha, Phuong; Grote, Tobias; Schafmeister, Frank; Böcker, Joachim (PCIM Europe digital days 2020)
An onboard DC-DC converter connects the high voltage traction battery to the low voltage auxiliary battery of an EV. It has to provide power across a wide range of input and output voltages. This paper presents the design and evaluation of an economical two-stage converter concept consisting of a first-stage boost converter and a second-stage LLC converter. While for low input voltages, the boost converter can supply the second-stage LLC with the optimum bulk voltage, for high input voltages, the boost converter is turned off and the LLC regulates the output voltage on its own. Whereas this is unproblematic for high output currents, for low loads high switching frequencies become necessary. For this purpose, the LLC needs to be designed for a wide gain range. Traditionally, this is achieved through a small magnetizing inductance resulting in increased conduction losses. If an asymmetric duty cycle operation is used to cover the low gains at low output current, the LLC can be optimized for a better efficiency. A prototype design proves that the asymmetric duty cycle operation is feasible to achieve a wide gain range at a high efficiency whereas the conventional design achieves very poor efficiencies.

LLC Converter Design in Capacitive Operation utilizes ZCS for IGBTs – a Concept Study for a 2.2 kW Automotive DC-DC Stage - Urbaneck, Daniel; Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (PCIM Europe digital days 2020)
LLC resonant converters generally employ MOSFETs in the inverter stage, which can be of half-bridge (HB) or full-bridge (FB) type. The generally weak intrinsic (body) diodes of the MOSFETs cause turn-on losses when being forced to hard current commutations finally leading to the components self-destruction when operated constantly in this way. Consequently, zero-voltage switching (ZVS) operation is more or less essential in a silicon (Si) MOSFET-based HB or FB. To ensure ZVS, the LLC is operated in the inductive region, i.e. with lagging resonant current. On the contrary, IGBTs show dominant turn-off losses and therefore are conventionally not applied in LLCs typically requiring high switching frequencies to achieve low output voltages. Yet, if the LLC is intentionally designed for the capacitive region, i. e. operation with leading current, zero-current switching (ZCS) enabling IGBTs in the inverter stage can be ensured. This paper explores in detail the LLC in the capacitive operating region and gives design considerations for a capacitive LLC utilizing both robust and cost-efficient IGBTs for an exemplary 2.2 kW automotive on-board DC-DC converter application. The results of a loss analysis show that the LLC resonant converter can be operated well in the capacitive region. In the given case, significantly lower overall and 30 % lower inverter stage losses are achieved in the thermally relevant worst-case comparison with an inductive LLC based on Si MOSFETs.

Comparison of Gray-Box and Black-Box Two-Level Three-Phase Inverter Models for Electrical Drives - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Industrial Electronics)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Accurate Torque Estimation for Induction Motors by Utilizing Globally Optimized Flux Observers - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (2020 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Towards a Scalable and Flexible Simulation and Testing Environment Toolbox for Intelligent Microgrid Control - Bode, Henrik; Heid, Stefan; Weber, Daniel; Hüllermeier, Eyke; Wallscheid, Oliver (arXiv:2005.04869)
Micro- and smart grids (MSG) play an important role both for integrating renewable energy sources in conventional electricity grids and for providing power supply in remote areas. Modern MSGs are largely driven by power electronic converters due to their high efficiency and flexibility. Nevertheless, controlling MSGs is a challenging task due to highest requirements on energy availability, safety and voltage quality within a wide range of different MSG topologies. This results in a high demand for comprehensive testing of new control concepts during their development phase and comparisons with the state of the art in order to ensure their feasibility. This applies in particular to data-driven control approaches from the field of reinforcement learning (RL), whose stability and operating behavior can hardly be evaluated a priori. Therefore, the OpenModelica Microgrid Gym (OMG) package, an open-source software toolbox for the simulation and control optimization of MSGs, is proposed. It is capable of modeling and simulating arbitrary MSG topologies and offers a Python-based interface for plug & play controller testing. In particular, the standardized OpenAI Gym interface allows for easy RL-based controller integration. Besides the presentation of the OMG toolbox, application examples are highlighted including safe Bayesian optimization for low-level controller tuning.

Perché celebrare Hegel? La sua dialettica è un brand, il suo pensiero una febbre benefica - Ficara, Elena; d'Agostini, Franca (La Stampa)

Lebanidze, Giorgi, Hegel’s Transcendental Ontology, New York 2019 - Ficara, Elena (Journal of the History of Philosophy)

Was ist die transzendentale Deduktion der Kategorien? - Ficara, Elena (Die Kategoriendeduktion in der Klassischen Deutschen Philosophie)

The Blushing Liar - Ficara, Elena; d'Agostini, Franca (Philosophia)

Truth and Incompatibility - Ficara, Elena (Reading Brandom. On A Spirit of Trust)

OMG: A scalable and flexible simulation and testing environment toolbox for intelligent microgrid control - Heid, Stefan; Weber, Daniel; Bode, Henrik; Hüllermeier, Eyke; Wallscheid, Oliver (Journal of Open Source Software)

Towards a scalable and flexible simulation and testing environment toolbox for intelligent microgrid control - Bode, Henrik; Heid, Stefan; Weber, Daniel; Hüllermeier, Eyke; Wallscheid, Oliver (arXiv preprint arXiv:2005.04869)

Permanent magnet synchronous machine temperature estimation using low-order lumped-parameter thermal network with extended iron loss model - Gedlu, Emebet Gebeyehu; Wallscheid, Oliver; Böcker, Joachim (The 10th International Conference on Power Electronics, Machines and Drives (PEMD 2020))

A Process to Develop Lean Big-Data Platform Architectures for Industrial Manufacturing Contexts - Illian, Marvin; Althoff, Simon; Karl, Holger (2020 25th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Berücksichtigung der Herstellungshistorie von Blechbauteilen beim Fügen durch Umformen - Wiesenmayer, Sebastian; Heyser, Per; Nehls, Thomas; Frey, Philipp; Flügge, Wilko; Meschut, Gerson; Merklein, Marion (Werkstattstechnik Online)

Determinants of nursing home choice: Does reported quality matter? - Schmitz, Hendrik; Stroka‐Wetsch, Magdalena A. (Health Economics)
Keywords: Health Policy

Determinants of nursing home choice: Does reported quality matter? - Schmitz, Hendrik; Stroka‐Wetsch, Magdalena A. (Health Economics)
Keywords: Health Policy

Trust development in care robots by opinion leader in the society - Thommes, Kirsten; Johansson-Pajala, Rose-Marie; Gustaffson, Christine; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Melkas, Helinä; Hoppe, Julia Amelie (Gerontechnology)

The fast and the furious—An experimental investigation of the pace of life and risky speed choice in traffic - Goldbach, Carina; Hoffmann, Christin; Hoppe, Julia Amelie; Pitz, Thomas; Thommes, Kirsten (PloS ONE)

Using loss aversion to incentivize energy efficiency in a principal agent context - Evidence from a field experiment - Hoffmann, Christin; Thommes, Kirsten (Economics Letters)

Combining Egalitarian and Proportional Sharing rules in Team Tournaments to Incentivize Energy-Efficient Behavior in a Principal-Agent Context - Hoffmann, Christin; Thommes, Kirsten (Organization & Environment)

Embedding care robots into society and practice: Socio-technical considerations - Pekkarinen, Satu; Hennala, Lea; Tuisku, Outi; Gustafsson, Christine; Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Melkas, Helina (Futures)

Forward-Secure 0-RTT Goes Live: Implementation and Performance Analysis in QUIC - Dallmeier, Fynn; Drees, Jan P.; Gellert, Kai; Handirk, Tobias; Jager, Tibor; Klauke, Jonas; Nachtigall, Simon; Renzelmann, Timo; Wolf, Rudi (Cryptology and Network Security)
Modern cryptographic protocols, such as TLS 1.3 and QUIC, can send cryptographically protected data in “zero round-trip times (0-RTT)”, that is, without the need for a prior interactive handshake. Such protocols meet the demand for communication with minimal latency, but those currently deployed in practice achieve only rather weak security properties, as they may not achieve forward security for the first transmitted payload message and require additional countermeasures against replay attacks.Recently, 0-RTT protocols with full forward security and replay resilience have been proposed in the academic literature. These are based on puncturable encryption, which uses rather heavy building blocks, such as cryptographic pairings. Some constructions were claimed to have practical efficiency, but it is unclear how they compare concretely to protocols deployed in practice, and we currently do not have any benchmark results that new protocols can be compared with.We provide the first concrete performance analysis of a modern 0-RTT protocol with full forward security, by integrating the Bloom Filter Encryption scheme of Derler et al. (EUROCRYPT 2018) in the Chromium QUIC implementation and comparing it to Google’s original QUIC protocol. We find that for reasonable deployment parameters, the server CPU load increases approximately by a factor of eight and the memory consumption on the server increases significantly, but stays below 400 MB even for medium-scale deployments that handle up to 50K connections per day. The difference of the size of handshake messages is small enough that transmission time on the network is identical, and therefore not significant.We conclude that while current 0-RTT protocols with full forward security come with significant computational overhead, their use in practice is feasible, and may be used in applications where the increased CPU and memory load can be tolerated in exchange for full forward security and replay resilience on the cryptographic protocol level. Our results serve as a first benchmark that can be used to assess the efficiency of 0-RTT protocols potentially developed in the future.

Practical Implementation and Verification of Simple-to-Implement Digital Current Observer for Half-Bridge Topologies - Ahmmad, Mohsin Ejaz; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM digital days))

Apparatus and method for charging an electric battery vehicle - Schafmeister, Frank

Influence of differing nozzle configurations on the final particle characteristics and particle structure evolution in spray flames - Tischendorf, Ricardo; Schmid, Hans-Joachim; Bieber, M.; Reddemann , M.; Kneer, R.; Fröde, F.; Grenga, T.; Pitsch, H.

Investigation of disturbance observers for model predictive current control in electric drives - Wallscheid, Oliver; Ngoumtsa, Etienne Florian Bouna (IEEE Transactions on Power Electronics)

Data Set Description: Identifying the Physics Behind an Electric Motor–Data-Driven Learning of the Electrical Behavior (Part II) - Hanke, Sören; Wallscheid, Oliver; Böcker, Joachim (arXiv preprint arXiv:2003.06268)

Data-Driven Permanent Magnet Temperature Estimation in Synchronous Motors with Supervised Machine Learning - Kirchgässner, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (arXiv preprint arXiv:2001.06246)

Numerical analysis of the robustness of clinching process considering the pre-forming of the parts - Bielak, Christian Roman; Böhnke, Max; Beck, Robert; Bobbert, Mathias; Meschut, Gerson (Journal of Advanced Joining Processes.)
Keywords: Clinching; process simulation; FEM; pre-straining; sensitivity analysis

Logik - Peckhaus, Volker (Gottfried Wilhelm Leibniz. Rezeption, Forschung, Ausblick)

Zermelo - Peckhaus, Volker (Neue Deutsche Biographie)

Dynamic Multi-Frequency Test Method for Hidden Interconnect Defects - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille
Keywords: WORKSHOP

Considering Context in Design Science Research: A Systematic Literature Review - zur Heiden, Philipp (Designing for Digital Transformation. Co-Creating Services with Citizens and Industry)

Kurt Gödel, Collected Works, Vol. IV: Correspondence A–G, Vol. V: Correspondence H. Ed. by Solomon Feferman et al. Oxford: Clarendon Press 2003 - Peckhaus, Volker (Historia Mathematica)

The Mathematical World of Charles L. Dodgson (Lewis Carroll). Edited by Robin Wilson and Amirouche Moktefi. Oxford University Press: Oxford 2019 - Peckhaus, Volker (British Journal for the History of Mathematics)

The Continued Exercise of Reason. Public Addresses by George Boole. Edited by Brendan Dooley. The MIT Press: Cambridge, Mass. and London, Engl. 2018 - Peckhaus, Volker (Isis)

Conference Report on the Digital Congress of the German Sociological Association: ‘Society under Pressure’ - Kastein, Mara (Gender and Research)

The Digitalization of Labour from a Gender Perspective (Gender and Research)

Grußwort - Peckhaus, Volker (Verleihung der Ehrendoktorwürde an Maria von Welser durch die Fakultät für Kulturwissenschaften der Universität Paderborn am 14. November 2019)

Stress state dependent damage modeling of self-pierce riveting process simulation using GISSMO damage model - Otroshi, Mortaza; Rossel, Moritz; Meschut, Gerson (Journal of Advanced Joining Processes)
Keywords: Self-pierce riveting; Ductile fracture; Damage modeling; GISSMO damage model

Joining of Thermoplastic Composites with Metals Using Resistance Element Welding (Applied Sciences)

Numerical investigation of the hole-drilling method applied to intrinsic manufactured metal-CFRP hybrids - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Proceedings of the 4th International Conference Hybrid 2020 Materials and Structures)

Determination and Validation of Residual Stresses in CFRP/Metal Hybrid Components Using the Incremental Hole Drilling Method - Wu, Tao; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang; Niendorf, Thomas (Journal of Composites Science)

Multikriterielle Betriebsstrategien industrieller Microgrids - Vogt, T.

De vriend, de wetenschapper: spanningsvelden in Yra van Dijks monografie over Arnon Grunberg - Lammer, Christina (Internationale Neerlandistiek)

Herausforderungen für die Chancengleichheit. Online-Mentoring für Studentinnen der Universität Paderborn - Lammer, Christina; Scharlau, Ingrid (Paderborner Universitätszeitschrift)

Kurzreferat über: Lungershausen, Gerrit: Weltkrieg mit Worten. Kriegsprosa im Dritten Reich 1933 bis 1940. Wiesbaden: J.B. Metzler 2017 - Willeke, Stephanie (Germanistik. Internationales Referatenorgan mit bibliographischen Hinweisen 61 (H. 1-2))

Der unzuverlässige Zeuge – Störungen im Erinnerungsdiskurs ‚Shoah‘ - Willeke, Stephanie (Trauma-Erfahrungen und Störungen des ‚Selbst‘. Mediale und literarische Konfigurationen lebensweltlicher Krisen)

Ludwig Tieck - Willeke, Stephanie (Vormärz-Handbuch)

Der literarische Weblog als digitales Gedächtnismedium – Erinnerungen als Schreib- und Rezeptionspraktiken in Benjamin Steins Turmsegler - Willeke, Stephanie (Inszenierung des Buchs im Internet (Medium Buch. Wolfenbütteler interdisziplinäre Forschungen))

Early Disclosure of Invention and Reduced Duplication: An Empirical Test - Lück, Sonja; Balsmeier, Benjamin; Seliger, Florian; Fleming, Lee (Management Science)
Much work on innovation strategy assumes or theorizes that competition in innovation elicits duplication of research and that disclosure decreases such duplication. We validate this empirically using the American Inventors Protection Act (AIPA), three complementary identification strategies, and a new measure of blocked future patent applications. We show that AIPA—intended to reduce duplication, through default disclosure of patent applications 18 months after filing—reduced duplication in the U.S. and European patent systems. The blocking measure provides a clear and micro measure of technological competition that can be aggregated to facilitate the empirical investigation of innovation, firm strategy, and the positive and negative externalities of patenting. This paper was accepted by Joshua Gans, business strategy.
Keywords: Management Science and Operations Research; Strategy and Management

A Knowledge Development Perspective on Literature Reviews: Validation of a New Typology in the IS Field - Schryen, Guido; Wagner, Gerit; Benlian, Alexander; Paré, Guy (Communications of the AIS)
Literature reviews (LRs) play an important role in the development of domain knowledge in all fields. Yet, we observe a lack of insights into the activities with which LRs actually develop knowledge. To address this important gap, we (1) derive knowledge building activities from the extant literature on LRs, (2) suggest a knowledge-based typology of LRs that complements existing typologies, and (3) apply the suggested typology in an empirical study that explores how LRs with different goals and methodologies have contributed to knowledge development. The analysis of 240 LRs published in 40 renowned IS journals between 2000 and 2014 allows us to draw a detailed picture of knowledge development achieved by one of the most important genres in the IS field. An overarching contribution of our work is to unify extant conceptualizations of LRs by clarifying and illustrating how LRs apply different methodologies in a range of knowledge building activities to achieve their goals with respect to theory.
Keywords: Literature review; knowledge development; knowledge building activities; knowledge-based typology; information systems research

High Performance Business Computing - Schryen, Guido; Kliewer, Natalia; Fink, Andreas (Business & Information Systems Engineering)

Deduktion und Abduktion beim diagrammatischen Schließen – das didaktische Potential der Peirceschen Semiotik - Schumacher, Jan

Recalculating Gravity: A Correction of Bergstrand's 1985 Frictionless Case - Stöckmann, Nico (Econ Journal Watch)

Spin splitting in a MoS2 monolayer induced by exciton interaction - Li, Yao; Li, Guangyao; Zhai, Xiaokun; Xiong, Shifu; Liu, Hongjun; Wang, Xiao; Chen, Haitao; Gao, Ying; Zhang, Xiu; Liu, Tong; Ren, Yuan; Ma, Xuekai; et al. (Physical Review B)

Kompetenzzuwachs und veränderte Unterrichtspraxis. Erste Ergebnisse aus der Evaluation eines DaZ-Weiterbildungsstudiums für Lehrkräfte an beruflichen Schulen - Böttger, Lydia; Groh, Olga; Otto, Lisa; Fischer, Nele; Hammer, Svenja; Jung, Ulla; Niederhaus, Constanze (Berufliche Integration durch Sprache. Reihe: Berichte zur beruflichen Bildung)

Integriertes Fach- und Sprachlernen in der beruflichen Bildung mittels Schreibwerkstatt für neu zugewanderte Lernende - Dohmann, Olga; Drumm, Sandra; Niederhaus, Constanze (Berufliche Integration durch Sprache)

Weiterbildendes Studium „Deutsch als Zweitsprache und Mehrsprachigkeit“ an der Universität Paderborn. Ausgestaltung und Evaluation einer Professionalisierungsmaßnahme im Bereich Inklusion - Berkel-Otto, Lisa; Böttger, Lydia; Fischer, Nele; Vasylyeva, Tetyana; Hammer, Svenja; Niederhaus, Constanze (Journal für Psychologie, 27(2))

A Set-Oriented Path Following Method for the Approximation of Parameter Dependent Attractors - Gerlach, Raphael; Ziessler, Adrian; Eckhardt, Bruno; Dellnitz, Michael (SIAM Journal on Applied Dynamical Systems)
In this work we present a set-oriented path following method for the computation of relative global attractors of parameter-dependent dynamical systems. We start with an initial approximation of the relative global attractor for a fixed parameter λ0 computed by a set-oriented subdivision method. By using previously obtained approximations of the parameter-dependent relative global attractor we can track it with respect to a one-dimensional parameter λ > λ0 without restarting the whole subdivision procedure. We illustrate the feasibility of the set-oriented path following method by exploring the dynamics in low-dimensional models for shear flows during the transition to turbulence and of large-scale atmospheric regime changes .

van Atten, Mark, "Essays on Gödel’s Reception of Leibniz, Husserl, Brouwer", Springer: Cham u.a. 2015 (Logic, Epistemology, and the Unity of Science, 35) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Jost, Jürgen, "Leibniz und die moderne Naturwissenschaft", Springer: Berlin 2019 (Wissenschaft und Philosophie) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Edwards-McKie, Susan, "On the infinite, in-potentia: discovery of the hidden revision of Philosophical Investigations and its relation to TS 209 through the eyes of Wittgenstein's Mathematics", in: Mras, Gabriele M. et al. (eds.), Philosophy of logic and mathematics. Proceedings of the 41. international Ludwig Wittgenstein Symposium, de Gruyter: Berlin 2019, 441-456 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Ramharter, Esther, "Der Status mathematischer und religiöser Sätze bei Wittgenstein", in: Mras, Gabriele M et al. (eds.), Philosophy of logic and mathematics. Proceedings of the 41. international Ludwig Wittgenstein Symposium, de Gruyter: Berlin 2019, 485-497 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard, "Mathematische Schriften 1804–1810", hg. v. Steve Russ und Edgar Morscher, Frommann-Holzboog, Eckhart Holzboog: Stuttgart-Bad Cannstatt 2020 (Bernard Bolzano-Gesamtausgabe. Reihe I: Schriften. Bd. 1) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Gedenkschrift für Jörg Riecke - Ptashnyk, Stefaniya (Wörter – Zeichen der Veränderung (Studia Linguistica Germanica))

Language Variation in multilingual historical settings - Ptashnyk, Stefaniya (“VARIATIONist Linguistics meets CONTACT Linguistics”)

In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, Hossein; Kormath Madam Raghupathy, Ramya; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas D. (Physical Chemistry Chemical Physics)
State-of-the-art methods in materials science such as artificial intelligence and data-driven techniques advance the investigation of photovoltaic materials.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Multi-Armed Bandits with Censored Consumption of Resources - Bengs, Viktor; Hüllermeier, Eyke (arXiv:2011.00813)
We consider a resource-aware variant of the classical multi-armed bandit problem: In each round, the learner selects an arm and determines a resource limit. It then observes a corresponding (random) reward, provided the (random) amount of consumed resources remains below the limit. Otherwise, the observation is censored, i.e., no reward is obtained. For this problem setting, we introduce a measure of regret, which incorporates the actual amount of allocated resources of each learning round as well as the optimality of realizable rewards. Thus, to minimize regret, the learner needs to set a resource limit and choose an arm in such a way that the chance to realize a high reward within the predefined resource limit is high, while the resource limit itself should be kept as low as possible. We derive the theoretical lower bound on the cumulative regret and propose a learning algorithm having a regret upper bound that matches the lower bound. In a simulation study, we show that our learning algorithm outperforms straightforward extensions of standard multi-armed bandit algorithms.

Einleitung - Ptashnyk, Stefaniya; Bopp, Dominika; Roth, Kerstin; Theobald, Tina (Wörter – Zeichen der Veränderung. Gedenkschrift für Jörg Riecke)

Coury, Aline Germano Foseca; Vilela, Denise Silva, “Russell’s Paradox: A Historical Study About the Paradox in Frege’s Theories”, In: Revista Brasileira de História da Mathématica 19, No. 37, 95–116 - Peckhaus, Volker (Mathematical Reviews)

Breger, Herbert, "Kontinuum, Analysis, Informales – Beiträge zur Mathematik und Philosophie von Leibniz", hg. v. W. Li, Springer Spektrum: Heidelberg/Berlin 2016 - Peckhaus, Volker (Mathematical Reviews)

Hanke, Miroslav, “The Probabilistic Logic of Eusebius Amort (1692–1775)”, In: Early Science and Medicine 24 (2019), 186–211 - Peckhaus, Volker (Mathematical Reviews)

Paakki, Jukka, "Arti Salomaa: Mathematician, Computer Scientist, and Teacher. A Thematic Biography", Springer: Cham 2019 - Peckhaus, Volker (Mathematical Reviews)

Spillover-Effekte der Sharing Economy - Rink, Lukas Max Johannes

Experimente in der Wirtschaftsinfromatik zu Kreativität - Ein systematischer Literaturüberblick und Implikationen für Geschäftsmodellmodellierungstools - Relard, Sebastian

Listen to theier Heart - Ein systematischer Literaturüberblick zur Rolle von Emotionen in nutzergenerierten Inhalten auf digitalen Plattformen - Helmert, Manuel Marc

Nothing comes for free - Ein klassifizierender Überblick zu den Auswirkungen finanzieller Anreize auf digitalen Märkten - Rosenhäger, Tjard Henrik

Stand der Forschung zu gefälschten Online-Bewertungen - Ein systematischer Literaturüberblick - Zauke, Simon

Visualisierung von Taxonomien: Ein systematischer Überblick - Kemadjou, Rostand Ndoumi

Digital Nudging - Ein systematischer Literaturüberblick - Droste, Jonas

Q&A for Products - Eine deskriptive Analyse von Fragen und Antworten auf digitalen Marktplätzen - Wegener, Maik

Taxonomie zu Taxonomie-Nutzungsgründen - Wolfförster, Lukas

Entwicklung und Vergleich von Messkriterien anhand statistischer Methoden zur Optimierung der Leistungserbringung im IT-Unternehmen Diebold Nixdorf im Global Service Delivery Management - Patzer, Christfof

Regiert Geld die AirBnb-Welt? Eine ökonometrische Analyse der Preisreaktionen von sozial- und finanziell motivierten AirBnb-Gastgebern auf politische Restriktionen - Müller, Michelle

Beziehungen innerhalb und zwischen Geschäftsmodellen: Systematische Analyse durch Geschäftsmodell-Modellierungssprachen - Dowbysch, Michael

Fanden Sie diese Bewertung nützlich? Ein Ansatz zur Vorhersage der Nützlichkeit von Online-Bewertungen - Löer, Christin

Is Delivery Killing Dine-In Restaurants?" - Eine ökonometrische Analyse von Spillover-Effekten für digitale Plattformen in der Restaurantindustrie - Philipp, Schumann

Eine strategische Analyse von Online-Kundenrezensionen zur Identifikation von Begeisterungsfaktoren mittels Latent Dirichlet Allocation - Kittsteiner, Anna Verena

Disziplin Schreibwissenschaft? Kritische Überlegungen zur Entwicklung einer „Practical Art“ - Girgensohn, Katrin; Haacke, Stefanie; Karsten, Andrea (Schreibwissenschaft - eine neue Disziplin: Diskursübergreifende Perspektiven)
Formiert sich eine Disziplin „Schreibwissenschaft“? Wir versuchen, die Form, den Gegenstand und mögliche Ziele des Feldes zu beschreiben, aus dem sich aktuell so etwas wie eine Disziplin zu bilden scheint. Nach einer Vergewisserung, was in der Wissenschaftssoziologie überhaupt unter Disziplin verstanden wird, arbeiten wir Spezifika einer Schreibwissenschaft als einer Practical Art heraus und diskutieren dann, welche Türen sich mit der Institutionalisierung einer Disziplin möglicherweise öffnen werden und welche sich vielleicht schließen.

Der Schreibprozess als Dialog. Eine Perspektive am Schnittpunkt von dialogischer Sprachwissenschaft und soziokultureller Psychologie - Karsten, Andrea (Schreibforschung interdisziplinär)

Oxidation/reduction cycles and their reversible effect on the dipole formation at CuInSe2 surfaces - Elizabeth, Amala; Sahoo, Sudhir K.; Lockhorn, David; Timmer, Alexander; Aghdassi, Nabi; Zacharias, Helmut; Kühne, Thomas; Siebentritt, Susanne; Mirhosseini, Hossein; Mönig, Harry (Phys. Rev. Materials)
The defect-electronic properties of {112} microfaceted surfaces of epitaxially grown CuInSe2 thin films are investigated by scanning tunneling spectroscopy and photoelectron spectroscopy techniques after various surface treatments. The intrinsic CuInSe2 surface is found to be largely passivated in terms of electronic defect levels in the band-gap region. However, surface oxidation leads to an overall high density of defect levels in conjunction with a considerable net surface dipole, which persists even after oxide removal. Yet, a subsequent annealing under vacuum restores the initial condition. Such oxidation/reduction cycles are reversible for many times providing robust control of the surface and interface properties in these materials. Based on ab initio simulations, a mechanism where oxygen dissociatively adsorbs and subsequently diffuses to a subsurface site is proposed as the initial step of the observed dipole formation. Our results emphasize the relevance of oxidation-induced dipole effects at the thin film surface and provide a comprehensive understanding toward passivation strategies of these surfaces.

In silico investigation of Cu(In,Ga)Se2-based solar cells - Mirhosseini, S. Hossein; Kormath Madam Raghupathy, Ramya; Sahoo, Sudhir K.; Wiebeler, Hendrik; Chugh, Manjusha; Kühne, Thomas (Phys. Chem. Chem. Phys.)
Photovoltaics is one of the most promising and fastest-growing renewable energy technologies. Although the price-performance ratio of solar cells has improved significantly over recent years{,} further systematic investigations are needed to achieve higher performance and lower cost for future solar cells. In conjunction with experiments{,} computer simulations are powerful tools to investigate the thermodynamics and kinetics of solar cells. Over the last few years{,} we have developed and employed advanced computational techniques to gain a better understanding of solar cells based on copper indium gallium selenide (Cu(In{,}Ga)Se2). Furthermore{,} we have utilized state-of-the-art data-driven science and machine learning for the development of photovoltaic materials. In this Perspective{,} we review our results along with a survey of the field.

A High-Rate Two-Dimensional Polyarylimide Covalent Organic Framework Anode for Aqueous Zn-Ion Energy Storage Devices - Yu, Minghao; Chandrasekhar, Naisa; Kormath Madam Raghupathy, Ramya; Ly, Khoa Hoang; Zhang, Haozhe; Dmitrieva, Evgenia; Liang, Chaolun; Lu, Xihong; Kühne, Thomas; Mirhosseini, S. Hossein; Weidinger, Inez M.; Feng, Xinliang (Journal of the American Chemical Society)
Rechargeable aqueous Zn-ion energy storage devices are promising candidates for next-generation energy storage technologies. However, the lack of highly reversible Zn2+-storage anode materials with low potential windows remains a primary concern. Here, we report a two-dimensional polyarylimide covalent organic framework (PI-COF) anode with high-kinetics Zn2+-storage capability. The well-organized pore channels of PI-COF allow the high accessibility of the build-in redox-active carbonyl groups and efficient ion diffusion with a low energy barrier. The constructed PI-COF anode exhibits a specific capacity (332 C g–1 or 92 mAh g–1 at 0.7 A g–1), a high rate capability (79.8% at 7 A g–1), and a long cycle life (85% over 4000 cycles). In situ Raman investigation and first-principle calculations clarify the two-step Zn2+-storage mechanism, in which imide carbonyl groups reversibly form negatively charged enolates. Dendrite-free full Zn-ion devices are fabricated by coupling PI-COF anodes with MnO2 cathodes, delivering excellent energy densities (23.9 ∼ 66.5 Wh kg–1) and supercapacitor-level power densities (133 ∼ 4782 W kg–1). This study demonstrates the feasibility of covalent organic framework as Zn2+-storage anodes and shows a promising prospect for constructing reliable aqueous energy storage devices.

Vibrational dynamics in lead halide hybrid perovskites investigated by Raman spectroscopy - Ibaceta-Jaña, Josefa; Muydinov, Ruslan; Rosado, Pamela; Mirhosseini, Hossein; Chugh, Manjusha; Nazarenko, Olga; Dirin, Dmitry N.; Heinrich, Dirk; Wagner, Markus R.; Kühne, Thomas; Szyszka, Bernd; Kovalenko, Maksym V.; et al. (Phys. Chem. Chem. Phys.)
Lead halide perovskite semiconductors providing record efficiencies of solar cells have usually mixed compositions doped in A- and X-sites to enhance the phase stability. The cubic form of formamidinium (FA) lead iodide reveals excellent opto-electronic properties but transforms at room temperature (RT) into a hexagonal structure which does not effectively absorb visible light. This metastable form and the mechanism of its stabilization by Cs+ and Br− incorporation are poorly characterized and insufficiently understood. We report here the vibrational properties of cubic FAPbI3 investigated by DFT calculations on phonon frequencies and intensities, and micro-Raman spectroscopy. The effects of Cs+ and Br− partial substitution are discussed. We support our results with the study of FAPbBr3 which expands the identification of vibrational modes to the previously unpublished low frequency region (<500 cm−1). Our results show that the incorporation of Cs+ and Br− leads to the coupling of the displacement of the A-site components and weakens the bonds between FA+ and the PbX6 octahedra. We suggest that the enhancement of α-FAPbI3 stability can be a product of the release of tensile stresses in the Pb–X bond, which is reflected in a red-shift of the low frequency region of the Raman spectrum (<200 cm−1).

Revealing the origin of the beneficial effect of cesium in highly efficient Cu(In,Ga)Se2 solar cells - Schöppe, Philipp; Schönherr, Sven; Chugh, Manjusha; Mirhosseini, Hossein; Jackson, Philip; Wuerz, Roland; Ritzer, Maurizio; Johannes, Andreas; Martínez-Criado, Gema; Wisniewski, Wolfgang; Schwarz, Torsten; T. Plass, Christian; et al. (Nano Energy)
The record conversion efficiency of thin-film solar cells based on Cu(In,Ga)Se2 (CIGS) absorbers has exceeded 23%. Such a high performance is currently only attainable by the incorporation of heavy alkali metals like Cs into the absorber through an alkali fluoride post-deposition treatment (PDT). As the effect of the incorporated heavy alkali metals is under discussion, we investigated the local composition and microstructure of high efficiency CIGS solar cells via various high-resolution techniques in a combinatory approach. An accumulation of Cs is clearly detected at the p-n junction along with variations in the local CIGS composition, showing the formation of a beneficial secondary phase with a laterally inhomogeneous distribution. Additionally, Cs accumulations were detected at grain boundaries with a random misorientation of the adjacent grains where a reduced Cu concentration and increased In and Se concentrations are detected. No accumulation was found at Σ3 twin boundaries as well as the grain interior. These experimental findings are in excellent agreement with complementary ab-initio calculations, demonstrating that the grain boundaries are passivated by the presence of Cs. Further, it is unlikely that Cs with its large ionic radius is incorporated into the CIGS grains where it would cause detrimental defects.